Safety monitoring and evacuation guide system for pipeline testing laboratory by indoor positioning technique and distributed sensor network - Lianhong Ding; Yu Xiao; Xiaotong Deng; Feng Li (International Journal of Distributed Sensor Networks)
To ensure the human’s safety in the large pipeline testing laboratory, a dynamic evacuation guide system is designed. Based on the analysis of various indoor position methods, inertial navigation system–aided ultra-wideband system is realized for human positioning. Gas sensors are deployed to monitor the leaking of harmful gases, such as H 2 S and CO. The gas diffusion area is also estimated dynamically based on the data of sensors. The evacuation route can be updated according to the real-time situation. Based on the positioning and warning method, a system is developed to dynamically plan safe evacuation route for human in different positions. The method and system can improve the safety of chemical laboratory and other environments with potential dangerous.